Pengaruh Pemberian Cannabinoid Pada Epilepsi yang Resisten Terhadap Pengobatan - Nabila Takeshita Dewi (Yayasan Pendidikan Medika Indonesia, 2020)
Cannabinoids are a potential therapeutic option for patients with treatment-resistant epilepsy. Anticonvulsant effect was obtained from Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (Δ9-THC). The method used by the author is literature study from several national and international journals. This method is used with the aim of presenting, increasing knowledge and understanding of this article by summarizing research material on a specific topic focus. From several studies conducted, it was found that CB1R, anandamide and synthetic cannabinoid WIN 55,212-2 mediators were activated as anticonvulsants.